Assessment of Cases of Cases of Mesenteric Ischaemia with MDCT - Praveen Kumar Monagari (Asian Journal of Medical Research, 2019)
Background: Mesenteric ischaemia comprises a complex, heterogeneous group of disorders that result in inadequate blood supply to the small or large bowel. The present study was conducted to assess the cases of mesenteric ischemia with MDCT. Subjects and Methods: The present study was conducted on 56 cases of mesenteric ischemia of both genders. 128 detector rows Siemens definition AS scanner was used for taking MDCT. Results: Out of 56 patients, males were 32 and females were 24. 26 cases were acute and 30 were chronic patients. The difference was non- significant (P- 0.5). MDCT shows bowel distention in 43 cases, bowel wall thickening in 37, SMA dissection in 48, pneumatosis in 13, SMA thrombosis in 17 and pneumoporta in 17 cases.  The difference was significant (P< 0.05). Conclusion: Authors found that MDCT is a newer and best diagnostic tool for the detection of mesenteric ischaemia. Bowel changes are well and accurately seen with MDCT.